Facilitating teachers’ professional learning in open class: a qualitative case study in China - Jinxiu Wu; Ping Shen (Humanities & Social Sciences Communications)
Abstract Open class is a public-oriented pedagogical practice aimed at enhancing teachers’ professional learning in China. This study examines how teachers conduct the open class and explores how open class facilitates the professional development of teachers. Through fieldwork at Sailing School and semi-structured interviews with nineteen teachers, four distinct phases of participation were identified: beginning (preparation for a show), presentation (using performance strategies), ending (evaluating teachers’ performance), and teamwork (cooperating with peers and students). Open class fosters four key forms of professional learning: enhancing the ability of instructional design, developing PCK in practice, fostering a pedagogical tact, and improving theoretical skills. The findings underscore open class as a platform to bridge the gap between practice and theory, while also highlighting a shift in teacher values from individualism to collectivism in open classes.